Mechanism and Parameters Controlling the Decomposition Kinetics of Na2SiF6 Powder to SiF4. Issue 7 (July 2016) - Soltani, N.; Pech‐Canul, M. I.; González, L. A.; Bahrami, A.
ABSTRACT: Sodium hexafluorosilicate (Na2 SiF6 ) powder has been used as a silicon source for formation of Si3 N4 coatings by the hybrid precursor system‐chemical vapor deposition (HYSY‐CVD) route. The quantitative effect of processing time, temperature, gas flow rate, and process atmosphere (N2 and N2 :5% NH3 ) upon the fractional weight loss during the decomposition of Na2 SiF6 was studied using a standard L9 Taguchi experimental design and analysis of variance. The decomposition kinetics of Na2 SiF6 (s) was studied theoretically and experimentally in the temperature range of 550–650ºC by applying the shrinking core model. It was found that regardless of atmosphere type, the reaction order is n ≈ 0.12 and that a two‐stage mixed mechanism consisting of chemical reaction and boundary layer gas transfer controls the decomposition rate. The determined fractional weight loss during Na2 SiF6 decomposition in nitrogen atmosphere is about 1.05–1.5 orders of magnitude greater than that in N2 :NH3 . The gas flow rate affects the dissociation activation energy, being of 121, 109, and 94 kJ/mol in N2 and of 140, 120, and 115 kJ/mol in N2 :NH3, for the flow rates of 20, 60, and 100 cm 3 /min, respectively, in both atmosphere types. A good agreement is observed by comparing experimental weight loss data with model predictions.